(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Wrongful convictions never occur when judges can be trusted to make fair decisions. Everywrongful conviction was the product of a deliberate procedure involving law enforcement officers,prosecutors, and perhaps both trial and appellate level judges. Even though authors have condemnedprosecutors, police detectives, defence lawyers, and lab workers for their roles in wrongful convictions,judges have often been given a pass. Judges are often portrayed in the news and other forms ofbroadcast media as unbiased, apolitical individuals who possess exceptional intelligence, wisdom, andcompassion and care deeply that justice is served in every circumstance while sitting in their highpositions, which may explain why they are not more involved in the community. But in reality, thingsseem quite different from that rosy picture